2020
DOI: 10.29309/tpmj/2020.27.10.4384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anti-inflammatory agent like Bryophyllum pinnatum aqueous extract and diclofenac on blood pressure and creatinine clearance.

Abstract: Objectives: To study the impact of anti-inflammatory agent like Bryophyllum pinnatum aqueous extract and diclofenac on blood pressure and creatinine clearance. Study Design: Experimental study. Setting: Sargodha Medical College, Sargodha, Department of Pharmacy, University of Sargodha. Period: 1st January 2019 to 30th June 2019. Material & Methods: 24 Sprague Dawley rats were obtained and were then divided into four groups. Negative control group (A) contained animals received normal diet while Group B, C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In accordance with this study, intra-peritoneal injection of diclofenac has shown a significant (p <0.001) rise in blood pressure of hypertensive rats. 20 In another study, diclofenac has shown increase in blood pressure of elderly human volunteers with a p value of 0.08. 21 These results are contrary to a study in which diclofenac did not change blood pressure of hypertensive rats 22 which may be because of a very small dose (1mg/kg) of diclofenac given for fifteen days.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In accordance with this study, intra-peritoneal injection of diclofenac has shown a significant (p <0.001) rise in blood pressure of hypertensive rats. 20 In another study, diclofenac has shown increase in blood pressure of elderly human volunteers with a p value of 0.08. 21 These results are contrary to a study in which diclofenac did not change blood pressure of hypertensive rats 22 which may be because of a very small dose (1mg/kg) of diclofenac given for fifteen days.…”
Section: Discussionmentioning
confidence: 95%
“…26 Another study has shown similar non-significant decrease in creatinine clearance in rats after diclofenac treatment. 20 Had the study been conducted for longer duration, results of serum creatinine and creatinine clearance may have become significant.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, leaf extract as well as root extract inhibited xanthinoxidase ( Latif et al, 2020 ; Morais Fernandes et al, 2021 ). 3-O-α-L-Arabinopyranosyl-(1→ 2)-O-α-L-rhamnopyranoside was shown to inhibit phosphodiesterase 4 (PDE4) ( Lourenço et al, 2020 ) and the antiplatelet effect of the aqueous extract indicated an effect on the arachidonic acid pathway (as does the inhibition of COX) ( Naqvi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%